Effect of Flowering Stages on the Content of Active Ingredients and Antioxidant Capability of Bletilla striata Flowers. Issue 2 (26th January 2023) - Wang, Zhen; Liu, Xinting; Wang, Jie; Fan, Zepeng; Shen, Jiayu; Chen, Yuanxing; Shao, Qingsong; Zheng, Ying
Abstract: Bletilla striata (Thunb.) Reichb.f. is a perennial herb with abundant active ingredients. Previous research mainly focused on its tubers, however, the study on flowers, especially the variation of active ingredient contents at different flowering stages, was rarely seen. This study analyzed the total phenols, flavonoids, polysaccharides, anthocyanins, and cyanidin‐3‐O‐glucoside content of B. striata flowers which were in cultivated in Herb Garden of Zhejiang A&F University and collected in May, 2019, in order to investigate the changes in active ingredients and antioxidant capacity among different flowering stages (bud, initial, and full bloom). Changes in radical scavenging capability of DPPH (1, 1‐Diphenyl‐2‐picrylhydrazyl radical), ABTS (2, 2′‐azinobis(3‐ethylbenzthiazoline‐6‐sulphonate)), and hydroxy were analyzed. Significant differences in active ingredient content of flowers were detected among different flowering stages. The total phenolic content increased continuously during the entire flowering stage. The contents of total flavonoid, total polysaccharide, and cyanidin‐3‐O‐glucoside reached peaks at the initial blooming stage and then fell as the flowering process continued. The antioxidant activity in initial stage was the highest than in any other flowering stages. Therefore, we conclude that the initial blooming stage is the best harvesting stage of B. striata flowers. This study provides a robust basis for the harvest and utilization of B. striata flowers in food, medical, and cosmetic industries. Abstract :